ANALISIS PROBLEMATIKA PEMBELAJARAN BAHASA DAN SASTRA INDONESIA BERBASIS DIGITAL DI MASA PANDEMI COVID-19 - Haerul Haerul Haerul; Yusrina Yusrina (STKIP Siliwangi, 2021)
The presence of Covid-19 has affected various aspects of life around the world. One aspect that is greatly affected by this virus is the aspect of education. Digital-based distance education is one of the policies carried out by the government in Indonesia so that education continues. However, in the actualization of digital-based learning, there were many complaints from various groups, especially from students. The purpose of this study was to analyze the problems of digital-based learning during the Covid-19 pandemic. The object used as a source of data analysis in this study is the problem of learning Indonesian language and literature. This research was conducted using a qualitative descriptive method, which describes the problems experienced by students when participating in digital-based Indonesian language and literature learning. The results of this study indicate that digital-based learning problems are found from various aspects, both from lecturers, students, and aspects of the digital-based learning media used. Description of digital-based learning problems during the pandemic as a result of this research is very useful for the development of teaching creativity and it can be concluded that various aspects of digital-based learning still need to be improved and developed.